Effectiveness of Fluoride Treatments in Remineralizing Early Non- Cavitated Carious Lesions: A Systematic Review and Meta-Analysis - Marwaha, Jasmine; Goud, Sindhoori; Dash, Manoranjan; Shadangi, Preeti Y; Arya, Ashtha; Minz, Aafreen Smriti (Bangladesh Journal of Medical Science, 2026)
Dental caries affects billions globally, with early non-cavitated lesions being reversible through fluoride remineralization. Despite extensive research, optimal fluoride protocols remain debated. This analysis aimed to evaluate the efficacy of fluoride treatments in remineralizing early caries and compare delivery methods, concentrations, and frequencies. This PRISMAcompliant systematic review included 12 RCTs and controlled trials (n=11,701 observations) from seven databases. Studies were assessed using ROB2/ROBINS-E tools, with metaanalyses conducted via random-effects models. Subgroup analyses explored fluoride types, concentrations, and follow-up durations. Highconcentration fluoride varnishes (≥5,000 ppm) showed the largest effects (ES=1.12, 95%CI: 0.88–1.36), while daily toothpastes (1,000–4,999 ppm) had more modest but consistent results (ES=0.93, 95%CI: 0.72–1.14). Network metaanalysis revealed a non-linear dose-response, with diminishing returns above 10,000 ppm. Professional applications every 3–6 months, combined with daily home care, emerged as the optimal regimen. Heterogeneity was substantial (I²=74.09%) but explained by concentration differences (27.12% variance). Fluoride effectively remineralizes early caries, with highconcentration professional treatments yielding superior outcomes. A combined approach of periodic in-office varnishes and daily toothpaste is recommended for comprehensive caries management. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue 2026, Page : S50-S62